JHEA, Volume 8, n°2, 2010 - Full Issue - Journal System (Journal of Higher Education in Africa, 2010)
Contents Colour-line: The Petrifaction of Racialization and Alterity at the University of Stellenbosch Fazil Moradi ........................................... 1 Algérie : le rapport savoir-pouvoir ou le rêve avorté de la différenciation par le savoir Hocine Khelfaoui .......................................... 23 A Neglected Impediment to True Africanisation of African Higher Education Curricula: Same Agenda, Differential Fee Regimes Chinedou. I. O. Okeke ............................... 39 The Academy and its Disengagement from Popular Struggles in Kenya Godwin R. Murunga.................................. 53 Crystalising Commitment to Transformation in a South African Higher Education Institute Helen M. Macdonald ........................................ 73 A Tension Between Massification and Intensification Reforms and Implications for Teaching and Learning in Ethiopian Public Universities Solomon Areaya........................................ 95